2007
DOI: 10.1080/14794800008520169
|View full text |Cite
|
Sign up to set email alerts
|

Representing and Understanding Multiplication

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 10 publications
0
7
0
14
Order By: Relevance
“…It may be assumed that by the end of primary school (age 11), all students in English mainstream education will have encountered rectangular arrays (both dots and grids), and that these representations will have been employed in the context of multiplication. This pedagogical practice is supported by recent findings that the array form has particularly good potential for supporting reasoning and developing understanding in multiplication, and is one of the best for demonstrating the commutative and distributive principles (Harries & Barmby, 2007). have identified various levels of sophistication in students' interaction with rectangular arrays of squares, and studies by Mitchelmore (2000, 2004) have linked increased regularity of structure observed in young children's 2D array drawings to their development of multiplicative strategies.…”
Section: D and 3d Arrays As Visuospatial Representations Of Multiplimentioning
confidence: 77%
See 1 more Smart Citation
“…It may be assumed that by the end of primary school (age 11), all students in English mainstream education will have encountered rectangular arrays (both dots and grids), and that these representations will have been employed in the context of multiplication. This pedagogical practice is supported by recent findings that the array form has particularly good potential for supporting reasoning and developing understanding in multiplication, and is one of the best for demonstrating the commutative and distributive principles (Harries & Barmby, 2007). have identified various levels of sophistication in students' interaction with rectangular arrays of squares, and studies by Mitchelmore (2000, 2004) have linked increased regularity of structure observed in young children's 2D array drawings to their development of multiplicative strategies.…”
Section: D and 3d Arrays As Visuospatial Representations Of Multiplimentioning
confidence: 77%
“…Furthermore, the flexibility to switch pragmatically between different array structurings can support understanding of further properties of multiplication (e.g. associativity or commutativity, as recommended by Harries & Barmby (2007)).…”
Section: Relationship Between Spatial Structuring and Enumeration In mentioning
confidence: 99%
“…[28], "a combination of a progress bar and a leaderboard is likely to generate excitement, commitment, a will to finish a gamified activity in a successful manner, and even desire to repeat the experience" (p. 38). Additional MG features that promote motivation include providing help in the form of hints and displaying graphical explanatory feedback correctly depicting the wrongly answered multiplication fact for commonly observed mistakes [84]. Motivation is also enhanced by timing players that can be available only for the case of older or highly skilled pupils, in order to provoke their interest and maintain their engagement.…”
Section: The Multiplication Gamementioning
confidence: 99%
“…In analysing the recordings obtained during the classroom sessions, we looked for ways in which the array supported or hindered children"s reasoning during multiplication calculations. In a previous paper (Harries & Barmby, 2007), we highlighted particular examples (by two pairs of children) of how the array might be used. In the following sections, we have looked in greater detail at the recordings and have categorised our observations, drawing on pupils" conversations as examples of their reasoning.…”
Section: Methodsmentioning
confidence: 99%